2020
DOI: 10.1093/ndt/gfaa217
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury e-alerts in pregnancy: rates, recognition and recovery

Abstract: Background Acute kidney injury (AKI) in pregnancy (Pr-AKI) is associated with substantial maternal morbidity and mortality. E-alerts are routinely used for detection of AKI in non-pregnant patients but their role in maternity care has not been explored. Methods All pregnant or postpartum women with AKI e-alerts for AKI Stages 1–3 (Kidney Disease Improving Global Outcomes (KDIGO) criteria) were identified at a tertiary centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
8
0
4
Order By: Relevance
“…The incidence of PR-AKI in this study far exceeded that reported in China [12]; in this study, the patients were enrolled on account of presenting with pathological obstetrics, and the incidence was also related to the severity of the patients' condition [26][27][28]. In this study, the APACHE II score was 8 (7-9) in Group B and 10 (8. in Group A.…”
Section: Discussionmentioning
confidence: 75%
“…The incidence of PR-AKI in this study far exceeded that reported in China [12]; in this study, the patients were enrolled on account of presenting with pathological obstetrics, and the incidence was also related to the severity of the patients' condition [26][27][28]. In this study, the APACHE II score was 8 (7-9) in Group B and 10 (8. in Group A.…”
Section: Discussionmentioning
confidence: 75%
“…11 Neither clinical nor laboratory criteria for AKI diagnosis in non-pregnant patients are fully validated in pregnant patients, but one early study has provided some useful data on the validity of them. 17 We asked if other patient groups were excluded and a notable 26% reported yes; with Paediatrics, Primary Care, OPDs, Renal Wards, Renal OPDs and ITUs listed. These additional exclusions were also contrary to the NHSE PSA.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11 Blood samples from people receiving dialysis or who are pregnant are exceptions to this recommendation. 8,10,11,17 Where possible, laboratories should develop processes to avoid reporting AKI in these patient populations. The AKI taskforce recognise it may not be feasible for many laboratories to exclude them, therefore exclusion by testrequest location, such as dialysis unit or maternity ward, may be more pragmatic 7 Laboratories must report AKI in both children and adults.…”
Section: Recommendationsmentioning
confidence: 99%
“…The significant association between the two cohorts for an increased risk for postpartum hemorrhage and cesarean delivery in women with AKI is not surprising because these are known risk factors for AKI. 22 Said another way, it is likely that the comorbid factor of postpartum hemorrhage contributed to AKI rather than the inverse. Perinatal outcomes were clinically similar and there were no differences in stillbirth or neonatal death rates, although these were relatively rare and our study may not be powered to detect these differences.…”
Section: Discussionmentioning
confidence: 99%